Rapid and Selective Determination of Folate Receptor α with Sensitive Resonance Rayleigh Scattering Signal - Liping Wu; Yue Liu; Rong Huang; Huawen Zhao; Weiqun Shu (International Journal of Analytical Chemistry)
A rapid, simple, and novel method for folate receptor α (FRα) determination is reported here. A probe of gold nanoparticles (Au NPs) modified with anti-FRα antibody was synthesized under the optimized conditions first. The antibody-modified Au NPs would aggregate when FRα was added to the probe for the specific interaction between antibody and antigen, resulting in the enhancement of resonance Rayleigh scattering (RRS) intensity. There is a linear relationship between the change of RRS intensity (ΔIRRS) and the concentration of FRα, with the detecting range of 0.50–37.50 ng·mL−1 and the limit of determination of 0.05 ng·mL−1. The determination of FRα in serum samples was realized with the advantages of high selectivity, high sensitivity, and easy operation.